Konsep Pendidikan Berbasis Masalah Paulo Freire dan Relevansinya dalam Projek Penguatan Profil Pelajar Pancasila: Paulo Freire's Problem-Based Education Concept and Its Relevance in the Project for Strengthening Pancasila Student Profiles - Sobon, Kosmas; Astari, Tri (Jurnal Filsafat Indonesia, 2024)
This research aims to analyse Paulo Freire's philosophy of education, especially the philosophy of problem-oriented education, and its relevance to the project of strengthening the student profile of Pancasila. This research seeks to find the meaning contained in Freire's philosophy of education through an in-depth interpretation of the implementation of an independent curriculum in Indonesia. The method used is library research with a hermeneutic approach. The results show that Freire's problem-based educational philosophy emerged as a response to bank-style education in Brazil. According to him, bank-style education is narrative, passive, oppresses society and has an impact on the culture of silence. Problem-based education focuses on teaching students to see the problems around them and to analyse them in order to find solutions. Freire's philosophy of problem-based education provides relevance for the implementation components of the Pancasila Learner Profile Strengthening Project, namely: the project must be problem-based, learner-centred, contextual, dialogical and exploratory.